2020
DOI: 10.1186/s12915-020-00822-3
|View full text |Cite
|
Sign up to set email alerts
|

Genomic architecture of endogenous ichnoviruses reveals distinct evolutionary pathways leading to virus domestication in parasitic wasps

Abstract: Background: Polydnaviruses (PDVs) are mutualistic endogenous viruses inoculated by some lineages of parasitoid wasps into their hosts, where they facilitate successful wasp development. PDVs include the ichnoviruses and bracoviruses that originate from independent viral acquisitions in ichneumonid and braconid wasps respectively. PDV genomes are fully incorporated into the wasp genomes and consist of (1) genes involved in viral particle production, which derive from the viral ancestor and are not encapsidated,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(65 citation statements)
references
References 92 publications
(179 reference statements)
0
65
0
Order By: Relevance
“…Interestingly, G. fumiferanae IVSPERs also contained at least three genes with conserved viral domains, namely a DNA polymerase, a D5 primase-helicase, and a DEXD helicase. Note that homologs for the last two genes were also recently described in H. didymator and C. sonorensis IVSPERs [30]. These domains are found in a set of genes conserved among nucleocytoplasmic large DNA viruses (NCLDVs), an observation that suggests the IV progenitor(s) could be from an uncharacterized or extinct viral taxon related to this group of viruses.…”
Section: A Campoplegine-related Virus-derived Machinery Involved In Banchine IV Productionmentioning
confidence: 73%
See 4 more Smart Citations
“…Interestingly, G. fumiferanae IVSPERs also contained at least three genes with conserved viral domains, namely a DNA polymerase, a D5 primase-helicase, and a DEXD helicase. Note that homologs for the last two genes were also recently described in H. didymator and C. sonorensis IVSPERs [30]. These domains are found in a set of genes conserved among nucleocytoplasmic large DNA viruses (NCLDVs), an observation that suggests the IV progenitor(s) could be from an uncharacterized or extinct viral taxon related to this group of viruses.…”
Section: A Campoplegine-related Virus-derived Machinery Involved In Banchine IV Productionmentioning
confidence: 73%
“…Furthermore, homologs to HdIV structural genes were identified in the calyx transcriptome of other IV-associated campoplegine wasps, namely Tranosema rostrale [19] and Bathyplectes sp. [24], or in the genome of C. sonorensis [30]. This clearly indicated that the set of virion structural genes was conserved among campoplegine wasps known to produce IVs.…”
Section: The Virus Ancestor and The Virus-derived Machinery Responsible For The Production Of Campoplegine IV Particlesmentioning
confidence: 81%
See 3 more Smart Citations